High-strength plastic zirconium alloy and preparation method thereof

By adjusting the content of Mo and Nb and powder metallurgy process, the problem of both strength and plasticity of zirconium alloy is solved, and a high-strength and high-plastic zirconium alloy material is realized, which is suitable for applications in multiple fields.

CN119307783APending Publication Date: 2025-01-14BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411448439.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing zirconium alloy materials are difficult to maintain high plasticity while increasing their strength, and cannot meet the dual needs of strength and plasticity, which limits their application in different fields.

Method used

By adjusting the content of Mo and Nb, the content of β phase in the zirconium alloy is increased, and the strength is increased through solid solution strengthening. At the same time, the content of Mo is controlled to avoid embrittlement, a zirconium alloy with high strength and high plasticity is prepared, using powder The metallurgical process is sintered to obtain a uniform metallographic structure.

Benefits of technology

The high dynamic compression strength and quasi-static compression strength of zirconium alloy have been improved, the critical strain rate has been greatly improved, and the strength and plasticity of the material have been significantly enhanced, which is suitable for a variety of application needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307783A_ABST
    Figure CN119307783A_ABST
Patent Text Reader

Abstract

The invention provides a high-strength plastic zirconium alloy and a preparation method thereof, and belongs to the technical field of zirconium alloy materials. The high-strength plastic zirconium alloy provided by the invention comprises the following chemical components in percentage by mass: 3-12% of Mo, 10-40% of Nb and the balance of Zr. By adding Nb and Mo elements, the content of a plastic beta phase in the zirconium alloy is increased, and the plasticity of the alloy is improved; moreover, the metal Nb, Mo and Zr can generate a solid solution strengthening effect, so that the strength of the zirconium alloy is improved; meanwhile, by controlling the content of Mo, the material strength can be greatly improved while the plasticity of the alloy is not reduced; by controlling the content of Nb, the beta-alpha phase transition temperature can be reduced, generation of coarse grains is avoided, and the alloy is mainly composed of a beta phase or even completely composed of the beta phase and has good strength and plasticity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zirconium alloy materials, and in particular to a high-strength and plastic zirconium alloy and a preparation method thereof. Background Art

[0002] Zirconium (Zr) is known as the "first metal of the atomic age". Zirconium has a low thermal neutron absorption cross-sectional area, excellent corrosion resistance in high-temperature and high-pressure water vapor, and good resistance to neutron irradiation. It is often used as a nuclear reactor structural material. Zirconium and its alloys are also used in the chemical industry because of their excellent corrosion resistance in most acids, alkalis and molten salts. At the same time, due to its good bone integration ability, low cytotoxicity and low magnetic susceptibility, it is used in biomedical materials.

[0003] The current zirconium alloy research mainly strengthens by adding trace alloying elements such as Ti, Nb, Mo, V, and Ta, but the strength is generally low, which makes it difficult to meet the demand for materials with high strength requirements. For example, the compressive strength of cast Zr50Nb50 is 1035MPa, and the failure strain is 16.4%; the compressive strength of Zr-6Nb is 881MPa, and the elongation at break is only 4.7%; the compressive strength of Zr-20Nb-xTi (x=0,3,7,11,15) is 1110~1307MPa, and the quasi-static failure strain is 37.62~38.10%.

[0004] Strength is mainly affected by factors such as the metal's crystal structure, lattice defects and grain boundaries, while plasticity is mainly affected by factors such as dislocation slip, twinning and grain boundary sliding of the metal's crystals. Generally speaking, metal materials with higher strength have poorer plasticity, and metal materials with better plasticity have lower strength. Therefore, how to improve the strength of zirconium alloy while ensuring the high plasticity of the alloy is a key factor in expanding the application range of zirconium alloy. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength and plastic zirconium alloy and a preparation method thereof. The zirconium alloy provided by the present invention has high dynamic strength and plasticity, meeting the application requirements of high-strength and plastic materials in different fields.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a high-strength and plastic zirconium alloy. The chemical composition of the high-strength and plastic zirconium alloy is as follows: 3-12% Mo, 10-40% Nb and the balance Zr, calculated by mass fraction.

[0008] Preferably, the chemical composition of the high-strength and plastic zirconium alloy is, by mass fraction, 5-8% Mo, 15-35% Nb, and the balance is Zr.

[0009] Preferably, the phase composition of the high-strength and plastic zirconium alloy is lath α phase and equiaxed β phase, or lath α phase, equiaxed β phase and Mo 2 Zr strengthening phase.

[0010] The present invention also provides a method for preparing the high-strength and high-plasticity zirconium alloy according to the above technical solution, comprising the following steps:

[0011] 1) mixing alloy raw material powders and pressing them into a shape to obtain an alloy blank;

[0012] 2) Sintering the alloy blank obtained in step 1) to obtain a high-strength and plastic zirconium alloy.

[0013] Preferably, the mixing method in step 1) includes any one of ball milling, V-type mixing, double cone mixing, three-dimensional mixing and double motion mixing.

[0014] Preferably, the ball-to-material ratio of the ball mill is 2:1 to 6:1, the rotation speed is 100 to 300 r / min, and the time is 5 to 8 hours.

[0015] Preferably, the compression molding method in step 1) is cold isostatic pressing, the pressure of the cold isostatic pressing is 200-400 MPa, and the holding time is 10-60 min.

[0016] Preferably, the sintering method in step 2) is solid phase sintering at normal pressure, and the sintering atmosphere is argon.

[0017] Preferably, in step 2), the sintering temperature is 1300-1700° C., and the holding time is 2-5 hours.

[0018] Preferably, after sintering in step 2), the temperature is lowered, and during the cooling process, the argon flow rate is set to reduce the temperature of the alloy from 800° C. to 300° C. at a rate of 8 to 10° C. / min.

[0019] The present invention provides a high-strength and plastic zirconium alloy, and the chemical composition of the high-strength and plastic zirconium alloy is: Mo 3-12%, Nb 10-40%, and the balance is Zr, in terms of mass fraction. The present invention is beneficial to increasing the content of plastic β phase in the zirconium alloy and improving the plasticity of the alloy by adding Nb and Mo elements; moreover, metal Nb, Mo and Zr will produce a solid solution strengthening effect to improve the strength of the zirconium alloy; at the same time, by controlling the content of Mo, the material strength can be greatly improved without reducing the plasticity of the alloy; by controlling the content of Nb, the β-α phase transition temperature can be reduced to avoid the generation of coarse grains, and the alloy is mainly composed of β phase or even completely composed of β phase, and has good strength and plasticity. The results of the embodiment show that the quasi-static compression strength of the high-strength and plastic zirconium alloy provided by the present invention is greater than 2500MPa, the critical strain is>50%, the dynamic compressive strength is 1700-2000MPa, and the critical failure strain is 5-35%. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a metallographic structure morphology of the high-strength and plastic zirconium alloy prepared in Example 1;

[0021] Figure 2 This is the XRD pattern of the high-strength and plastic zirconium alloy prepared in Example 1;

[0022] Figure 3 The quasi-static compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 1;

[0023] Figure 4 The dynamic compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 1;

[0024] Figure 5 This is a metallographic structure morphology of the high-strength and plastic zirconium alloy prepared in Example 2;

[0025] Figure 6 XRD diagram of the high-strength and plastic zirconium alloy prepared in Example 2;

[0026] Figure 7 The quasi-static compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 2;

[0027] Figure 8 The dynamic compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 2;

[0028] Fig. 9 This is a metallographic structure morphology of the high-strength and plastic zirconium alloy prepared in Example 3;

[0029] Fig.10 This is the XRD pattern of the high-strength and plastic zirconium alloy prepared in Example 3;

[0030] Fig.11The quasi-static compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 3;

[0031] Fig.12 The dynamic compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 3;

[0032] Fig.13 This is a metallographic structure morphology of the high-strength and plastic zirconium alloy prepared in Example 4;

[0033] Fig.14 XRD diagram of the high-strength and plastic zirconium alloy prepared in Example 4;

[0034] Fig.15 The quasi-static compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 4;

[0035] Fig.16 This is the dynamic compressive stress-strain curve of the high-strength and plastic zirconium alloy prepared in Example 4. DETAILED DESCRIPTION

[0036] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0037] The invention provides a high-strength and plastic zirconium alloy. The chemical composition of the high-strength and plastic zirconium alloy is as follows: 3-12% Mo, 10-40% Nb and the balance Zr, calculated by mass fraction.

[0038] In the present invention, the mass fraction of Mo in the high-strength and plastic zirconium alloy is 3% to 12%, preferably 4% to 10%, and more preferably 5% to 8%. In the present invention, the Mo and Zr produce a solid solution strengthening effect to improve the strength of the zirconium alloy; at the same time, limiting the mass fraction of Mo within the above range can reduce the high-strength but brittle intermetallic compound Mo formed by Mo and Zr. 2 The Zr phase content greatly improves the alloy strength without reducing the alloy plasticity.

[0039] In the present invention, the mass fraction of Nb in the high-strength and plastic zirconium alloy is 10% to 40%, preferably 12% to 37%, and more preferably 15% to 35%. In the present invention, the Nb and Zr produce a solid solution strengthening effect to improve the strength of the zirconium alloy; at the same time, the lattice distortion produced by the solid solution strengthening of Nb is relatively small, which can avoid the reduction of the alloy plasticity caused by large lattice distortion, and ensure the plasticity of the alloy to a certain extent while improving the strength. The present invention limits the mass fraction of Nb to the above range, which can reduce the β-α phase transition temperature and avoid the generation of coarse grains. The alloy is mainly composed of β phase or even completely composed of β phase, and has good strength and plasticity.

[0040] In the present invention, the phase composition of the high-strength and plastic zirconium alloy is preferably a lath α phase and an equiaxed β phase, or a lath α phase, an equiaxed β phase and Mo 2 Zr strengthening phase; the content of the equiaxed β phase is higher than the content of the lath α phase.

[0041] The present invention adds Nb and Mo elements, which are beneficial to increasing the content of plastic β phase in zirconium alloy and improving the plasticity of the alloy. At the same time, they can also produce solid solution strengthening effect with Zr to improve the strength of zirconium alloy. In addition, the addition of Mo element can also form trace high-strength intermetallic compound Mo 2 Zr phase greatly improves the strength of the alloy without reducing the plasticity of the alloy.

[0042] The present invention also provides a method for preparing the high-strength and high-plasticity zirconium alloy according to the above technical solution, comprising the following steps:

[0043] 1) mixing alloy raw material powders and pressing them into a shape to obtain an alloy blank;

[0044] 2) Sintering the alloy blank obtained in step 1) to obtain a high-strength and plastic zirconium alloy.

[0045] The invention mixes alloy raw material powders and then presses them into shape to obtain an alloy blank.

[0046] In the present invention, the alloy raw material powder preferably includes Zr powder, ZrH 2 Zirconium is an active element, and its powder surface is easily oxidized. The introduction of excessive oxygen will lead to oxidation of the material on the one hand, and the oxide layer will seriously hinder the diffusion of elements and interface migration during the sintering process on the other hand, resulting in uneven material structure and poor density. The present invention uses zirconium hydride as a zirconium source. On the one hand, it utilizes the diffusion of H atoms to increase the diffusion rate of Zr and Nb atoms, thereby achieving low-cost pressureless sintering densification of the material. On the other hand, it utilizes the hydrogen release of hydrides during the sintering process to provide a micro-reducing atmosphere for sintering, thereby reducing the oxygen content in the alloy.

[0047] In the present invention, the particle size of the Zr powder is preferably 10 to 45 μm, and the purity is preferably greater than 99.9%. 2 The particle size of the powder is preferably 10-45 μm, and the purity is preferably greater than 99.5%. The particle size of the Nb powder is preferably 10-45 μm, and the purity is preferably greater than 99.9%. The particle size of the Mo powder is preferably 10-45 μm, and the purity is preferably greater than 99.9%.

[0048] In the present invention, the mixing method preferably includes any one of ball milling, V-type mixing, double cone mixing, three-dimensional mixing and double motion mixing, and is more preferably ball milling. In the present invention, the ball-to-material ratio of the ball milling is preferably 2:1 to 6:1, the ball milling speed is preferably 100 to 300 r / min, and the ball milling time is preferably 5 to 8 hours. In the present invention, the speed of the V-type mixing is preferably 20 to 50 r / min, and the mixing time is preferably 8 to 24 hours. By mixing the alloy raw material powders, each raw material powder can be evenly dispersed to ensure the uniform performance of the final alloy.

[0049] When ball milling is used for mixing, the present invention has no special requirements for the equipment of the ball milling, and the equipment commonly used in the art can be used. In the embodiment of the present invention, a high-energy ball mill is preferred.

[0050] In the present invention, the press forming method is preferably cold isostatic pressing, and the pressure of the cold isostatic pressing is preferably 200-400 MPa, more preferably 250-350 MPa. The present invention limits the pressure of press forming to the above range, which can promote contact and diffusion between powders, increase the density of the alloy blank, and further improve the performance of the alloy.

[0051] In the present invention, the holding time of the cold isostatic pressing is preferably 10 to 60 minutes, more preferably 10 to 45 minutes. The holding time of press molding affects product quality and performance. The present invention limits the holding time to the above range, which is beneficial to further improve the strength and plasticity of the zirconium alloy.

[0052] After obtaining the alloy blank, the present invention sintered the alloy blank to obtain a high-strength and plastic zirconium alloy.

[0053] In the present invention, the sintering method is preferably atmospheric solid phase sintering. In the present invention, a protective gas is preferably introduced before the sintering, and the protective gas is preferably argon. In the present invention, the protective gas can prevent the alloy from contacting with oxygen during the sintering process, causing oxidation of the alloy.

[0054] In the invention, the sintering temperature is preferably 1300-1700°C, more preferably 1350-1650°C; the sintering heating rate is preferably 4-6°C / min; the sintering holding time is preferably 2-5h, more preferably 3-4h. The sintering parameters of the alloy affect the microstructure, mechanical properties and physical properties of the alloy. Within the parameter range defined by the present invention, it is beneficial to further improve the strength and plasticity of the zirconium alloy.

[0055] After sintering, the present invention preferably cools the sintered alloy, and in the cooling process, preferably, the argon gas flow rate is set to reduce the alloy from 800°C to 300°C at a cooling rate of 8 to 10°C / min. The present invention can avoid the precipitation of a large amount of grain boundary α phase or the embrittlement of the material caused by residual stress by controlling the cooling rate, thereby further improving the plasticity of the alloy.

[0056] The present invention has no special requirements for the sintering equipment, as long as the alloy blank can be sintered. In the embodiment of the present invention, a sintering furnace is preferred.

[0057] The preparation method provided by the present invention is simple, comprising the steps of mixing alloy raw material powders to obtain a uniformly mixed mixed powder; pressing the mixed powders to obtain an alloy blank; and sintering the alloy blank to obtain a zirconium alloy. A high-strength, high-plasticity zirconium alloy with uniform and dense structure is prepared by adopting a powder metallurgy process. The process can realize batch production and can be pressed into blanks of various shapes and sizes. The process is efficient, the material utilization rate is high, the cost is low, and it is conducive to industrial production.

[0058] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] Example 1

[0060] A high-strength and plastic zirconium alloy has a chemical composition of Zr-35Nb-5Mo, namely, 35% Nb, 5% Mo and the remainder Zr by mass fraction.

[0061] The preparation method is as follows:

[0062] Take Zr and ZrH with an average particle size of 10 μm respectively 2 The Nb and Mo powders were prepared according to the alloy composition Zr-35Nb-5Mo and mixed in a high-energy ball mill with a ball-to-material ratio of 2:1 and a ball mill speed of 200 r / min for 6 hours to obtain a mixed powder.

[0063] The mixed powder is pressed by cold isostatic pressing at a pressure of 350 MPa and a holding time of 15 min to obtain an alloy blank;

[0064] The alloy blank is solid-phase sintered in an argon protective atmosphere with a heating rate of 5°C / min, a sintering temperature of 1500°C, a holding time of 4h, and then cooled to 800°C in the furnace and then the cooling rate is controlled to be 10°C / min to obtain a high-strength and plastic zirconium alloy.

[0065] The metallographic structure of high-strength and plastic zirconium alloys observed using a scanning electron microscope, such as Figure 1 As shown in the figure, it can be seen that the alloy is composed of large pieces of continuously distributed bright gray β phase and lath-like distributed dark gray α phase. The lath α phase is mainly distributed at the β phase grain boundaries and inside the grains.

[0066] The crystal phase structure of the high-strength and plastic zirconium alloy was analyzed by X-ray diffractometer, and the XRD pattern was as follows: Figure 2 As shown in the figure, it can be seen that the alloy is composed of α phase and β phase, and the peak intensity of β phase is higher than that of α phase, indicating that the content of β phase is higher than that of α phase.

[0067] The obtained high-strength and plastic zirconium alloy was subjected to quasi-static compression test (10 -3 s -1 ), using Origin software, the quasi-static stress-strain curve is obtained as follows Figure 3 As shown in the figure, it can be seen that the sample did not fail at 3200 MPa, indicating that the compressive strength is higher than 3200 MPa and the critical strain is greater than 50%.

[0068] The obtained high-strength and ductile zirconium alloy was subjected to dynamic compression test using a split Hopkinson pressure bar (SHPB) with a strain rate of 4000s -1 , using D-wave and Origin software, the dynamic stress-strain curve is obtained as follows Figure 4 As shown, the data was read from the test software: the compressive strength reached 1614MPa, and the critical failure strain reached 35%.

[0069] Example 2

[0070] A high-strength and plastic zirconium alloy has a chemical composition of Zr-30Nb-3Mo, namely, 30% Nb, 3% Mo and the remainder Zr by mass fraction.

[0071] The preparation method is as follows:

[0072] Take Zr and ZrH with an average particle size of 10 μm respectively 2 The Nb and Mo powders were prepared according to the alloy composition Zr-30Nb-3Mo and mixed in a high-energy ball mill with a ball-to-material ratio of 4:1 and a ball mill speed of 200 r / min for 6 h to obtain a mixed powder.

[0073] The mixed powder is pressed by cold isostatic pressing at a pressure of 350 MPa and a holding time of 15 min to obtain an alloy blank;

[0074] The alloy blank is solid-phase sintered in an argon protective atmosphere with a heating rate of 5°C / min, a sintering temperature of 1500°C, a holding time of 4h, and then cooled to 800°C in the furnace and then the cooling rate is controlled to be 10°C / min to obtain a high-strength and plastic zirconium alloy.

[0075] The metallographic structure of high-strength and plastic zirconium alloys observed using a scanning electron microscope, such as Figure 5 As shown in the figure, it can be seen that the alloy is composed of large pieces of continuously distributed bright gray β phase and lath-like distributed dark gray α phase. The lath α phase is small in length and width and is concentrated at the β phase grain boundaries. There is very little lath α phase distributed inside the grains.

[0076] The crystal phase structure of the high-strength and plastic zirconium alloy was analyzed by X-ray diffractometer, and the XRD pattern was as follows: Figure 6 As shown in the figure, it can be seen that the alloy is composed of α phase and β phase, and the peak intensity of β phase is higher than that of α phase, indicating that the content of β phase is higher than that of α phase.

[0077] The obtained high-strength and plastic zirconium alloy was subjected to quasi-static compression test (10 -3 s -1 ), using Origin software, the quasi-static stress-strain curve is obtained as follows Figure 7 As shown in the figure, it can be seen that the sample did not fail at 3297 MPa, indicating that the compressive strength is higher than 3297 MPa and the critical strain is greater than 50%.

[0078] The obtained high-strength and ductile zirconium alloy was subjected to dynamic compression test using a split Hopkinson pressure bar (SHPB) with a strain rate of 4000s -1 , using D-wave and Origin software, the dynamic stress-strain curve is obtained as follows Figure 8 As shown, the data was read from the test software: the compressive strength reached 1753MPa, and the critical failure strain reached 18.8%.

[0079] Example 3

[0080] A high-strength and plastic zirconium alloy has a chemical composition of Zr-15Nb-12Mo, namely, Nb 15%, Mo 12% and the balance Zr by mass fraction.

[0081] The preparation method is as follows:

[0082] Take Zr and ZrH with an average particle size of 10 μm respectively 2 The Nb and Mo powders were prepared according to the alloy composition Zr-15Nb-12Mo and mixed in a high-energy ball mill with a ball-to-material ratio of 2:1 and a ball mill speed of 200 r / min for 6 hours to obtain a mixed powder.

[0083] The mixed powder is pressed by cold isostatic pressing at a pressure of 350 MPa and a holding time of 15 min to obtain an alloy blank;

[0084] The alloy blank is solid-phase sintered in an argon protective atmosphere with a heating rate of 5°C / min, a sintering temperature of 1500°C, a holding time of 4h, and then cooled to 800°C in the furnace and then the cooling rate is controlled to 8°C / min to obtain a high-strength and plastic zirconium alloy.

[0085] The metallographic structure of high-strength and plastic zirconium alloys observed using a scanning electron microscope, such as Fig. 9 As shown in the figure, it can be seen that the alloy consists of a bright gray β phase and a dark gray α phase distributed in a lath-like manner. The lath α phase is concentrated at the β phase grain boundary and inside the grains, and the bright white dendritic Mo 2 Zr phase precipitates along the grain boundaries.

[0086] The crystal phase structure of the high-strength and plastic zirconium alloy was analyzed by X-ray diffractometer, and the XRD pattern was as follows: Fig.10 As shown in the figure, it can be seen that the alloy consists of α phase, β phase and Mo 2 Zr phase composition.

[0087] The obtained high-strength and plastic zirconium alloy was subjected to quasi-static compression test (10 -3 s -1 ), using Origin software, the quasi-static stress-strain curve is obtained as follows Fig.11 As shown in the figure, it can be seen that the sample did not fail at 2799 MPa, indicating that the compressive strength is higher than 2799 MPa and the critical strain is greater than 50%.

[0088] The obtained high-strength and ductile zirconium alloy was subjected to dynamic compression test using a split Hopkinson pressure bar (SHPB) with a strain rate of 4000s -1 , using D-wave and Origin software, the dynamic stress-strain curve is obtained as follows Fig.12 As shown, the data was read from the test software: the compressive strength reached 1746MPa, and the critical failure strain reached 5.0%.

[0089] Example 4

[0090] A high-strength and plastic zirconium alloy has a chemical composition of Zr-30Nb-10Mo, namely, Nb 30%, Mo 10% and the balance Zr by mass fraction.

[0091] The preparation method is as follows:

[0092] Take Zr and ZrH with an average particle size of 10 μm respectively 2The Nb and Mo powders were prepared according to the alloy composition Zr-30Nb-10Mo and mixed in a high-energy ball mill with a ball-to-material ratio of 2:1 and a ball mill speed of 200 r / min for 6 hours to obtain a mixed powder.

[0093] The mixed powder is pressed by cold isostatic pressing at a pressure of 350 MPa and a holding time of 15 min to obtain an alloy blank;

[0094] The alloy blank is solid-phase sintered in an argon protective atmosphere with a heating rate of 5°C / min, a sintering temperature of 1500°C, a holding time of 4h, and then cooled to 800°C in the furnace and then the cooling rate is controlled to 8°C / min to obtain a zirconium alloy.

[0095] The metallographic structure of high-strength and plastic zirconium alloys observed using a scanning electron microscope, such as Fig.13 As shown in the figure, it can be seen that the alloy is composed of bright gray β phase and dark gray α phase distributed in lath shape. The lath α phase is concentrated at the β phase grain boundary, and the lath α phase distributed inside the grain is less. 2 Zr phase precipitates in large quantities along the grain boundary α phase.

[0096] The crystal phase structure of the high-strength and plastic zirconium alloy was analyzed by X-ray diffractometer, and the XRD pattern was as follows: Fig.14 As shown in the figure, it can be seen that the alloy consists of α phase, β phase and Mo 2 The Zr phase is composed, and the peak intensity of the β phase is higher than that of the α phase, indicating that the content of the β phase is higher than that of the α phase.

[0097] The obtained high-strength and plastic zirconium alloy was subjected to quasi-static compression test (10 -3 s -1 ), using Origin software, the quasi-static stress-strain curve is obtained as follows Fig.15 As shown in the figure, it can be seen that the sample did not fail at 2566MPa, indicating that the compressive strength is higher than 2566MPa and the critical strain is greater than 50%.

[0098] The obtained high-strength and ductile zirconium alloy was subjected to dynamic compression test using a split Hopkinson pressure bar (SHPB) with a strain rate of 4000s -1 , using D-wave and Origin software, the dynamic stress-strain curve is obtained as follows Fig.16 As shown, the data was read from the test software: the compressive strength reached 1906MPa, and the critical failure strain reached 10.8%.

[0099] It can be seen from the above embodiments and comparative examples that the present invention helps to increase the content of plastic β phase in zirconium alloy and improve the plasticity of the alloy by adding Nb and Mo elements; moreover, metal Nb, Mo and Zr will produce a solid solution strengthening effect and improve the strength of the zirconium alloy.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength and plastic zirconium alloy, wherein the chemical composition of the high-strength and plastic zirconium alloy is, by mass fraction, 3-12% Mo, 10-40% Nb, and the remainder Zr.

2. The high-strength and plastic zirconium alloy according to claim 1, characterized in that: Calculated by mass fraction, the chemical composition of the high-strength and plastic zirconium alloy is: Mo 5-8%, Nb 15-35%, and the balance is Zr.

3. The high-strength and ductile zirconium alloy according to any one of claims 1 to 2, characterized in that: The phase composition of the high-strength and plastic zirconium alloy is a lath α phase and an equiaxed β phase, or a lath α phase, an equiaxed β phase and a Mo2Zr strengthening phase.

4. The method for preparing a high-strength and plastic zirconium alloy according to any one of claims 1 to 3, characterized in that: The steps include: 1) mixing alloy raw material powders and pressing them into a shape to obtain an alloy blank; 2) Sintering the alloy blank obtained in step 1) to obtain a high-strength and plastic zirconium alloy.

5. The preparation method according to claim 4, characterized in that: The mixing method in step 1) includes any one of ball milling, V-type mixing, double cone mixing, three-dimensional mixing and double motion mixing.

6. The preparation method according to claim 5, characterized in that: The ball-to-material ratio of the ball mill is 2:1-6:1, the rotation speed is 100-300 r / min, and the time is 5-8 hours.

7. The preparation method according to claim 4, characterized in that: The pressing method in step 1) is cold isostatic pressing, the pressure of the cold isostatic pressing is 200-400 MPa, and the holding time is 10-60 min.

8. The preparation method according to claim 4, characterized in that: The sintering method in step 2) is solid phase sintering at normal pressure, and the sintering atmosphere is argon.

9. The preparation method according to claim 4 or 8, characterized in that: In the step 2), the sintering temperature is 1300-1700° C., and the holding time is 2-5 hours.

10. The preparation method according to claim 4, characterized in that: After sintering in step 2), the temperature is lowered. During the cooling process, the argon gas flow rate is set to reduce the temperature of the alloy from 800° C. to 300° C. at a rate of 8 to 10° C. / min.